Effect of auditory temporal training program on speech fluency of children with developmental stuttering - Farazi, Morteza; Hosseini dastgerdi, zahra; Lotfi, Yones; Moossavi, Abdollah; Bakhshi, Enayatollah (Iranian Journal of Child Neurology, 2023)
Objectives to investigate the effect of auditory temporal processing training on the alleviation of stuttering severity in children who stutter (CWS) diagnosed with auditory temporal processing (ATP) disorders. Materials & Methods Thirty-one (31) CWS diagnosed with ATP disorders participated in this study (intervention group: 17 participants between 7 to 12 years old; control group: 14 participants between 8 to 12 years old). The ATP test and SSI-3 were examined before, after 12 sessions (about 540 minutes) training, and three months following the conclusion of the intervention. Result According to the results, ATP improved significantly in the intervention group after auditory temporal training and the differences between the intervention and control group were significant (p<0.05). The improvement of ATP skills remained stable in the post-training evaluation after three months (p>0.05). Although the SSI-3 score was further improved in the intervention group, but there was no significant difference between two groups (p=0.984). Conclusions The findings revealed that ATP training acted as a complementary therapy alleviating stuttering severity of CWS with ATP disorders to some extent.